2017
DOI: 10.1167/tvst.6.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Reveals Changes to Corneal Reflectivity and Thickness in Individuals with Tear Hyperosmolarity

Abstract: PurposeTo investigate whether tear hyperosmolarity, a feature of dry eye disease (DED), affects central corneal thickness (CCT), corneal light reflectivity, and/or tear film reflectivity.MethodsThis prospective, cross-sectional study involved 48 participants (38 with hyperosmolar tears and 10 controls with normo-osmolar tears). Symptoms and signs of DED (tear osmolarity, sodium fluorescein tear break-up time, ocular surface staining, Schirmer test) were assessed. CCT, and the reflectivity of the cornea and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Tear film-corner interface reflectivity has been shown to be higher in eyes with hyperosmolar tears compared to control eyes. 29 Other studies involving dry eye and OCT have shown that there is a positive correlation between tear film measurements from OCT and the Schirmer's test, as well as, showing high reproducibility of tear film measurements using OCT. 30 , 31 …”
Section: Discussionmentioning
confidence: 91%
“…Tear film-corner interface reflectivity has been shown to be higher in eyes with hyperosmolar tears compared to control eyes. 29 Other studies involving dry eye and OCT have shown that there is a positive correlation between tear film measurements from OCT and the Schirmer's test, as well as, showing high reproducibility of tear film measurements using OCT. 30 , 31 …”
Section: Discussionmentioning
confidence: 91%
“…25 Another study of symptomatic, hyperosmolar patients (327.6 ± 2.8 mOsm/L, 34.6 ± 2.1 OSDI, 0.51 ± 0.1 staining, 8.1 ± 0.8 TBUT, 11.8 ± 1.5 Schirmers) found significantly lower corneal stromal reflectivity as measured by OCT in hyperosmolar eyes relative to controls (p < 0.05) and significantly thinner central corneal thickness in the upper quartile of hyperosmolar eyes (539.1 ±7.4 µm than in control eyes (583.1 ±15.0 µm, P = 0.02) or in the lower quartile of hyperosmolar subjects (622.7 ± 5.8 µm, P < 0.0001). 47 In the absence of other observable signs of dry eye disease, hyperosmolarity is, by itself, predictive of surgical complications and altered corneal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, dry eye disease is associated with reduced corneal thickness . This relationship between corneal thickness and dry eye disease has been confirmed in dry eye patients with elevated tear osmolarity, with a negative linear relationship existing between central corneal thickness, as measured by Fourier‐domain OCT, and tear osmolarity greater than 316 mOsmol/l . To date, these findings have not yet been replicated in animal models of dry eye disease, possibly owing to the subtle nature of the response.…”
Section: As‐oct Imaging In Animalsmentioning
confidence: 99%